Corrosion mechanism and hydrogen evolution on Mg. Issue 2 (April 2015) - Thomas, S.; Medhekar, N.V.; Frankel, G.S.; Birbilis, N.
Highlights: The corrosion mechanism for Mg has been reviewed in light of contemporary works employing advanced analytics. Mg dissolution occurs via an n  = 2 mechanism, at open circuit and during anodic polarisation. Hydrogen evolution accompanying Mg dissolution is a persistent cathodic reaction. A phenomenological model for Mg dissolution is presented, accounting for enhanced catalytic behaviour. Abstract: Magnesium (Mg) dissolution is distinct from other engineering metals, as Mg can support cathodic hydrogen evolution on its surface during anodic polarisation. The phenomenon of cathodic hydrogen evolution upon anodically polarised Mg is characterised by the rate of the hydrogen evolution reaction (HER) increasing with anodic polarisation, a phenomenon called the negative different effect (NDE). Mg has a tendency to aggressively corrode in aqueous solutions, impairing its application as a durable engineering material or a predictable electrode material, which is also influenced by the NDE. Over the last century a number of different theories have sought to explain the NDE. However, recent progress in research upon Mg utilising contemporary methods including advanced electrochemical techniques, on-line elemental analysis and cross-sectional electron microscopy, have not only refined the understanding of Mg dissolution, but discredited almost a century of alternate theories. During anodic polarisation, a bilayered MgO/Mg(OH)2 film forms on Mg, appearing as a dark region on visual inspection. This film gradually occupies the bulk of the previously pristine Mg surface, and importantly sustains (and enhances) the HER. This phenomenon of cathodic activation may also be catalysed by an enrichment of noble elements or impurities on the Mg surface, which could play an important role in promoting the HER. A phenomenological model for the dissolution of Mg encompassing the current opinion of many researchers is presented herein.